2022
DOI: 10.1021/acscatal.2c00477
|View full text |Cite
|
Sign up to set email alerts
|

CuII Lewis Acid, Proton-Coupled Electron Transfer Mechanism for Cu-Metal–Organic Framework-Catalyzed NO Release from S-Nitrosoglutathione

Abstract: Evidence is provided for a previously unknown proton-coupled electron transfer (PCET) mechanism for nitric oxide (NO) release from endogenous S-Nitrosoglutathione (GSNO) catalyzed by the metal−organic framework (MOF) H 3 [(Cu 4 Cl) 3 (BTTri) 8 ] (CuBTTri) in the presence of glutathione (GSH). The balanced reaction stoichiometry, active site characterization, and the experimental rate law are used to systematically disprove competing mechanistic hypotheses, leading unexpectedly to PCET as the proposed basic mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 78 publications
7
23
0
Order By: Relevance
“…More NO is generated for both the powder and the composite in a shorter amount of time with added GSH versus without (Table ). The observation of complete NO release within 2 h for the powder with added GSH is identical with the results we have reported previously and is in line with other findings that the reaction is first order in [GSH]. , The composite, however, still releases more NO in less time than the powder, requiring approximately 1/5th to 1/6th the time as the powder to achieve 100% NO recovery with added GSH.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…More NO is generated for both the powder and the composite in a shorter amount of time with added GSH versus without (Table ). The observation of complete NO release within 2 h for the powder with added GSH is identical with the results we have reported previously and is in line with other findings that the reaction is first order in [GSH]. , The composite, however, still releases more NO in less time than the powder, requiring approximately 1/5th to 1/6th the time as the powder to achieve 100% NO recovery with added GSH.…”
supporting
confidence: 92%
“…We explored this question by repeating the reactions with a stoichiometric amount of GSH added (Figure ) under otherwise identical conditions. It is known that the rate law for GSNO to NO conversion catalyzed by CuBTTri powder is first order in [GSH] with saturation kinetics observed at increased [GSH] . We reasoned that if a different GSNO to NO conversion reaction mechanism was at play in the MOF composite system than for the powder, it would be unlikely that the first order dependence on [GSH] would be preserved for the composite material.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The higher activity of ZZU-282 than UiO-66 suggested that ZZU-282 is a promising candidate for detoxifying nerve agents. To determine whether the catalytic activity might be due to the open metal sites of the Cu cluster, we examined the catalytic efficiency by potassium thiocyanate (KSCN) poisoning experiments. As depicted in Figures c, S17, and S18, the degradation of DECP dramatically declined to 42% upon the addition of KSCN, demonstrating that the copper sites in ZZU-282 played a dominant role in activating DECP. Then, a control experiment involving MOF-199 with an open channel structure and exposed Cu­(II) metal sites was conducted (Figure S19).…”
Section: Resultsmentioning
confidence: 99%